Pengembangan Model Bimbingan Pribadi Sosial untuk Mereduksi Perilaku Bullying Siswa di Madrasah Aliyah Negeri Polman - Saifuddin, Saifuddin (UI DDI AGH AD Polewali Mandar, 2017)
This research and development was conducted at MAN Polman. The subjects of the study were 6 students of class XI. the problem of study was the students of class XI who did the bullying. The study employed ADDIE research and development approach. data were collected through interview, direct observation, and questionnaire instrument. the data were analyzed qualitatively. the guidance of socio personal guidance model was tested to two experts, accepted and could be used as counselor guidance. the result from the expert was tested to students which showed students could comprehend socio personal guidance which could be implemented in the environment. the result of the study are (1) students at MAN Polman are identified as the victim as well as the doer of bullying. (2) produce socio personal guidance model to reduce students behavior in bullying and (3) the socio personal guidance model can be the guidance in implementing guidance and counseling, particularly to reduce students behavior in bullying.